Establishment and Characterization of a Topotecan Resistant Non-small Cell Lung Cancer NCI-H460/TPT10 Cell Line - Lei, Zi-Ning; Teng, Qiu-Xu; Zhang, Wei; Fan, Ying-Fang; Wang, Jing-Quan; Cai, Chao-Yun; Lu, Kimberly W.; Yang, Dong-Hua; Wurpel, John N. D.; Chen, Zhe-Sheng (Frontiers in Cell and Developmental Biology, 2020)
While topotecan (TPT) is a first- and second-line chemotherapeutic drug in treating lung cancer, the development of drug resistance in tumors still reserves as a major obstacle to chemotherapeutic success. Therefore, a better understanding of the mechanisms of topotecan resistance is critical. In this study, the first topotecan-resistant human non-small cell lung cancer (NSCLC) cell line, termed NCI-H460/TPT10, was established from the parental NCI-H460 cell line. NCI-H460/TPT10 cells exhibited a 394.7-fold resistance to TPT, and cross-resistance to SN-38, mitoxantrone, and doxorubicin, compared to parental NCI-H460 cells. Overexpression of ABCG2 localized on the cell membrane, but not ABCB1 or ABCC1, was found in NCI-H460/TPT10 cells, indicating that ABCG2 was likely to be involved in topotecan-resistance. This was confirmed by the abolishment of drug resistance in NCI-H460/TPT10 cells after ABCG2 knockout. Moreover, the involvement of functional ABCG2 as a drug efflux pump conferring MDR was indicated by low intracellular accumulation of TPT in NCI-H460/TPT10 cells, and the reversal effects by ABCG2 inhibitor Ko143. The NCI-H460/TPT10 cell line and its parental cell line can be useful for drug screening and developing targeted strategies to overcome ABCG2-mediated MDR in NSCLC.